Hybrid pedestrian and transit priority zoning policies in an urban street network: Evaluating network traffic flow impacts with analytical approximation. (October 2021) - Fournier, Nicholas
Abstract: Pedestrianized zones are becoming an increasingly popular policy tool for cities seeking to improve "walkability", "livability", and reduce congestion in the urban center by prohibiting automobiles from entering a designated zone. However, pedestrianized zones can be inappropriately implemented in locations without justifiable congestion or sufficient transit alternatives. For mixed-traffic transit (e.g., bus and light-rail streetcars), the lack of reasonable transit alternatives is an issue further compounded by the traffic congestion generated from diverted driving trips concentrated around the pedestrianized zone, inadvertently slowing down both automobile traffic and mixed-traffic transit in tandem. Alternatively, to mitigate the traffic congestion impact on transit, policy makers can also designate a "transit priority" zone around the pedestrian zone, where transit is unimpeded by congestion either through transit signal priority, dedicated lanes, or both. This ensures transit provides a consistent travel alternative as congestion varies, creating a stable demand equilibrium that would otherwise be suppressed by congestion. While such a solution has been proposed in advocacy, no research has explored such a combined policy in analytical terms. This research explores the potential complementary benefits and optimal sizing of pedestrianization and transit priority zones through analytical evaluation in an idealized rectilinear city. The model is intended to provide insights regarding traffic impacts, optimal zone sizing, system capacity, and the justifiable thresholds for implementing complementary pedestrianization and transit priority zones in a city.